2021
DOI: 10.1002/zoo.21601
|View full text |Cite
|
Sign up to set email alerts
|

The past, present and future of hormonal contraceptive use in managed captive female tiger populations with a focus on the current use of deslorelin acetate

Abstract: Tigers (Panthera tigris spp.) are endangered in the wild; ensuring sustainable insurance populations requires careful planning within zoological collections. In captive situations, contraceptives are often used to control breeding and ensure genetically viable populations that contain manageable numbers of animals; reversible contraceptives are ideal because they offer flexibility for breeding management. Historically, synthetic progestins, such as melengestrol acetate implants, were used in female tigers, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
2
1
Order By: Relevance
“…The rate of reversal post-deslorelin treatment observed among female ASCOs in this study (53.3%, N = 8/15) is comparable to that reported for tigers (55.6%, N = 10/18) [36] and across various other taxa (62.5%, N = 10/16) [19]. Traditionally, deslorelin implants are placed between the scapulae.…”
Section: Contraceptionsupporting
confidence: 80%
See 1 more Smart Citation
“…The rate of reversal post-deslorelin treatment observed among female ASCOs in this study (53.3%, N = 8/15) is comparable to that reported for tigers (55.6%, N = 10/18) [36] and across various other taxa (62.5%, N = 10/16) [19]. Traditionally, deslorelin implants are placed between the scapulae.…”
Section: Contraceptionsupporting
confidence: 80%
“…Our analyses also indicate that the time to reversal post-implant treatment was faster among females who had their implants removed. In contrast to this study, there was no association found between implant removal and reversal in tigers [36]. Cowl et al, 2018, found that placing deslorelin in alternative sites, such as the base of the ear or forelimb, had equivalent contraceptive efficacy and a higher rate of reversal compared with the traditional placement site (83.3% reversal rate vs. 50% reversal rate, respectively) [19].…”
Section: Contraceptioncontrasting
confidence: 74%
“…Big felids cared for in many zoos and sanctuary facilities breed so effectively that contraceptive methods are used to keep the population at a healthy size. Reproduction can be avoided by separating the sexes or through permanent sterilization [1], in addition to reversible contraception and gonadotropin-releasing hormone (GnRH) agonists [2][3][4][5],…”
Section: Introductionmentioning
confidence: 99%
“…progestins implants [6], and vaccines [7]. Although reversible contraception is desirable since it permits natural social groupings to be preserved while maintaining the population's genetic health [2], surgical contraception has been utilized in animals with various pathologies and medical disorders and in animals that should not be bred [1]. Furthermore, for individuals who are genetically well represented or for whom reproduction might entail potential health risks, permanent sterilization may be considered.…”
Section: Introductionmentioning
confidence: 99%